The Book in the Digital Library - Serra, Liliana (Cadernos de Educação Tecnologia e Sociedade, 2022)
Libraries are formed by printed book, e-books, etc. This article, a result of a bibliographical research carried out from 1993 to 2016, discusses the digital book in the library. At first, is made a distinction between virtual and digital libraries. The virtual library is formed by links, with the content arranged in Web sites. The digital library uses repositories to store the files and allows the collection of its metadata by service providers, from the use of the OAI-PMH protocol. The digital book is analyzed, with a brief history until the identification of typologies: static book, dynamic book, and expanded book. Digital books can be open or licensed content. When opened, they are stored in digital repositories. When licensed, a link directs the reader to the reading platform. Licensing is carried out through the application of business models, which may be perennial or transitory. The article concludes that e-books imply the construction of virtual and digital libraries. Virtual when the collection consists of licensed content, and digital when the titles are available in open formats.